Teachers and students interacting around the textbook - Ghosn, Irma K. (2001)
This research study was undertaken to address questions and concerns about the language teaching textbook as regards to its role in input, feedback, and production of learner output. Specifically, it investigates whether literature-based reading texts generate different interactions than traditional language teaching texts and whether the differences can be related to the development of academic L2 literacy.;Six grade five classes (163 students) were selected, three that use a traditional English language teaching textbook and three that use a course intended as reading instruction textbook for native English-speaking children. A standardized non-verbal reasoning test was administered at the beginning of the study to determine similarity of intellectual ability of the groups. Two fifty-minute class periods were videotaped in each class, once during the fall term and once during the spring term, and a total of 30 minutes of each class observation were transcribed. Samples of the textbooks were selected for analysis, and all students were administered a reading comprehension test toward the end of the academic year.;Data analysis comprised both quantitative and qualitative approaches. A total of 1158 teacher utterances and 544 student utterances were coded and frequency data collected. The frequency data were analyzed using Chi-square tests, and data from standardized tests were subjected to analysis of variance (ANOVA). The transcribed utterances were further analyzed using a qualitative approach in order to identify categories of interaction exchanges.;Findings indicate that interactions differ in classrooms using the two types of textbooks. Significant differences were found in teacher questions, student communication, and teacher feedback. Qualitative differences in classroom discourse were identified that can be related to the textbook type. The two groups differed significantly in general and specific subject-matter reading comprehension. Based on the findings, a model showing the complexity of classroom language learning is suggested for further investigation.